Through the looking glass: a qualitative study of film in First Nations communities - Lino, Amanda A. (2014)
This thesis explores the use of film and its effectiveness in capturing knowledge being transmitted from Elders to Youth while providing a ‘true’ indigenous voice. The research is based on a case study conducted with two Indigenous communities involved in the production of a research film about health and the environment, and employs interviews with community members, academics and filmmakers. In the case study, film is used for two purposes. For the researchers, the film is utilized as an anthropological analytic tool to capture ethnographic information (for academic purposes). The communities are employing film as a vehicle for intergenerational transmission of cultural knowledge. The results show that film can benefit both academics and participants based on these objectives. Film is a tool for ethnological insight and can be used to impart life lessons, traditional knowledge and history to future generations.